Real or Artificial? Intergroup Biases in Mind Perception in a Cross-Cultural Perspective - Krumhuber, Eva G. (PLoS One, 2015)
Recent research suggests that attributions of aliveness and mental capacities to faces are influenced by social group membership. In this article, we investigated group related biases in mind perception in participants from a Western and Eastern culture, employing faces of varying ethnic groups. In Experiment 1, Caucasian faces that ranged on a continuum from real to artificial were evaluated by participants in the UK (in-group) and in India (out-group) on animacy, abilities to plan and to feel pain, and having a mind. Human features were found to be assigned to a greater extent to faces when these belonged to in-group members, whereas out-group faces had to appear more realistic in order to be perceived as human. When participants in India evaluated South Asian (in-group) and Caucasian (out-group) faces in Experiment 2, the results closely mirrored those of the first experiment. For both studies, ratings of out-group faces were significantly predicted by participants’ levels of ethnocultural empathy. The findings highlight the role of intergroup processes (i.e., in-group favoritism, out-group dehumanization) in the perception of human and mental qualities and point to ethnocultural empathy as an important factor in responses to out-groups.